2004
DOI: 10.1097/00129334-200409000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Negative Pressure Wound Therapy in Open Foot Wounds with Significant Soft Tissue Defects

Abstract: Wound cavity filling time and time to complete closure were similar in both study groups, despite the fact that patients receiving NPWT were older, had larger wounds, and had poorer nutrition. NPWT may be an effective modality for the healing of open wounds with significant defects and for reducing subsequent care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 27 publications
1
28
1
1
Order By: Relevance
“…Wound closure (secondary healing or surgical closure) was described as the incidence of complete wound closure in 2 studies 20,22 and as the time to wound closure (complete or incomplete) in 7 studies 23,[26][27][28]31,36,37 (Table 3). Only 2 of the 5 RCTs 20,26 and 2 of the 4 non-RCTs 28,37 reported a significant advantage in favor of NPWT.…”
Section: Clinical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wound closure (secondary healing or surgical closure) was described as the incidence of complete wound closure in 2 studies 20,22 and as the time to wound closure (complete or incomplete) in 7 studies 23,[26][27][28]31,36,37 (Table 3). Only 2 of the 5 RCTs 20,26 and 2 of the 4 non-RCTs 28,37 reported a significant advantage in favor of NPWT.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Hospital stay was shortened by NPWT in 1 non-RCT 28 but was similar in 4 other nonRCTs. 31,32,34,35 An economic analysis was performed in 1 RCT, 24 yielding similar overall costs for NPWT and conventional therapy.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…The extensive studies on the established use of the VAC technique in the wound-healing phase of granulation have resulted in guidelines that recommend VAC therapy in acute and chronic wounds [7,8,9,10,11,12], burns [13], diabetic ulcers [14, 15] as well as open foot wounds [16], vasculitis- or occluding vasculopathy-induced ulcers [17]. However, there have been very few reports on the postoperative application of VAC therapy [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with NPWT, allowed these patients to be discharged from hospital and treated at home, where they could maintain greater mobility with improved quality of life. Within home healthcare settings, Page et al (2004) reported that NPWT may help to improve patient care…”
Section: Use Of Npwt In Primary Secondary and Acute Settingsmentioning
confidence: 99%